Assessment of seroprevalence against poliovirus among Italian adolescents and adults - Silvia Lupi; Armando Stefanati; Tatjana Baldovin; Alberto Roman; Vincenzo Baldo; Giovanni Gabutti (Taylor & Francis Group, 2019)
In 2002, the WHO European Region was declared polio-free. Nonetheless global eradication has not yet been completed and the reintroduction from at risk areas is still possible. This seroprevalence study evaluated samples collected from each Italian region in the 12−50 years old age range to assess protection against Poliovirus (PV) 1, 2 and 3 among subjects immunised with different vaccination schedules. 1073 samples (50.5% females) were examined. WHO standardized microneutralization assay was used. Seroprotection rates were 92.9%, 96.2% and 83.4%, for PV1, PV2 and PV3, respectively. Geometric Mean Titres (GMTs) were higher for PV2 (52.8) and PV1 (41.1) than for PV3 (21.0). Increasing the age, a decreasing trend in seropositivity was observed, in particular for PV3. The 2017-2019 Italian National Immunisation Plan emphasises, as primary objective, the maintenance of the polio-free status and strongly validates the 2 + 1 schedule in the first year of life with IPV vaccine associated with the administration of booster doses at 6 years and during the adolescence. Surveillance system and high population immunity are crucial to ensure the maintenance of polio-free status.